The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.aim.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Ricci flow under local almost non-negative curvature conditions

Abstract: We find a local solution to the Ricci flow equation under a negative lower bound for many known curvature conditions. The flow exists for a uniform amount of time, during which the curvature stays bounded below by a controllable negative number. The curvature conditions we consider include 2-non-negative and weakly PIC 1 cases, of which the results are new. We complete the discussion of the almost preservation problem by Bamler-Cabezas-Rivas-Wilking, and the 2-non-negative case generalizes a result in 3D by Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 17 publications
(20 reference statements)
0
29
0
Order By: Relevance
“…Moreover, for any 0 ≤ t ≤ γT , again using that γ − 1 2 ≤ ε, [Lai18]. Doing so gives us constants C 0 = C 0 (n, v 0 ) ≥ 1 and S 0 = S 0 (n, v 0 ) > 0 such that for all 0 < t ≤ min {γT, S 0 } the conclusion (3.2) hold for g γ (t) instead of g(t).…”
Section: Local Flows and Curvature Estimatesmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, for any 0 ≤ t ≤ γT , again using that γ − 1 2 ≤ ε, [Lai18]. Doing so gives us constants C 0 = C 0 (n, v 0 ) ≥ 1 and S 0 = S 0 (n, v 0 ) > 0 such that for all 0 < t ≤ min {γT, S 0 } the conclusion (3.2) hold for g γ (t) instead of g(t).…”
Section: Local Flows and Curvature Estimatesmentioning
confidence: 99%
“…We conclude this section by recording that it is possible to find a local solution to the Ricci flow, assuming a lower K IC 1 bound. This is the content of Theorem 1.1 in [Lai18]; we state a minor variant that is more convenient for our purposes. In particular, we reduce the initial noncollapsedness hypothesis to a lower volume bound for a single unit ball, rescale the result to apply to any ball of radius strictly larger than one, and add a lower injectivity radius bound to the conclusion.…”
Section: Local Flows and Curvature Estimatesmentioning
confidence: 99%
See 2 more Smart Citations
“…When the initial metric is Kähler with non-negative bisectional curvature, the author and Tam [21] were able to construct a short-time solution to the Kähler-Ricci flow. When the initial metric is only Riemannian and has almost weakly PIC 1 , Yi [20] showed that a short-time solution also exists. We also refer the earlier work by Bamler, Cabezas-Rivas and Wilking [2] for the case when g 0 has complex sectional curvature bounded from below or equivalently g 0 has almost weakly PIC 2 .…”
Section: Introductionmentioning
confidence: 99%